"Togetherness in Difference": Perceived Personal Discrimination and Acculturation Preferences among Internal Migrants in a Poor Urban Community in Accra. (March 2018) - Tutu, Raymond Asare; Boateng, John; Ameyaw, Edmund Essah; Busingye, Janice Desire
This paper assesses the relative effects of acculturation preferences (assimilation, separation, integration, and marginalization) on migrants' perception of acceptability in James Town, a traditional urban neighborhood in Accra, Ghana. There is a paucity of academic work on the relationship between migrants' acculturation inclinations and their assessment of the hosts' attitude towards them in Ghana. Cognizant of the fluidity of acculturation strategies, the study focuses on individual inclinations towards acculturation. To examine migrants' perception of acceptability by the host, we use perceived personal discrimination. We utilize results from a semi-structured questionnaire administered to 301 migrant individuals from different migrant households in James Town. Our findings suggest that migrants with assimilation preferences are less likely to have a higher rating on the extent to which they are discriminated against by the host population. Such an exploratory study is pertinent to understanding relationships (conflicts or "togetherness in difference") in poor multi-ethnic settings.